(untitled) (Parliamentary Studies, 2010)
The article is intended to analyze the practical problems of political communication, to wit the peculiarities and importance of rhetoric used by political leaders. The paper provides a review on the President D. Grybauskaitė’s rhetoric, itself an interesting and problematic case of Lithuanian political rhetoric. Further, a synopsis of the rhetoric of political leaders and presidents is set out, along with the role of rhetoric per se in the processes of political communication.